Sexual harassment in the workplace: an evaluation of selected higher learning institutions' policies and procedures - Mthimkhulu, Busisiwe (My University, 2021)
Sexual harassment in the workplace is a plague. Workplaces, in all their forms and magnitudes are increasingly being affected by sexual harassment. Higher learning institutions are no exception. Higher learning institutions form the microcosm of society and are thus worth being placed under scrutiny. The higher learning institutions, by virtue of their composition, activities and structure mirror characteristics of that of a workplace. It is thus important that the role of labour law, which is ensuring that employers provide for a safe working environment is upheld. This paper focuses on three South African higher learning institutions, from the perspective of labour law in evaluating their policies and procedures. Labour law requires that workplaces should have policies and procedures to combat sexual harassment, thus becomes crucial to evaluate the extent to which they are legally compliant and effective. Although, there are various forums and mechanisms to curb sexual harassment, policies and procedures of workplaces remain an important factor in providing for a framework and strategy to eradicate sexual harassment. It is thus paramount that higher learning institutions have effective policies and procedures in place to tackle the plague that is sexual harassment. The shortcoming often arises when even in the midst of well-drafted policies and procedures in the workplace, sexual harassment does not cease to exist. In order to uphold the objective of labour law for a safe working environment, these high learning institutions ought to ensure that the policies are not only well-drafted but also, legally complaint and effective
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Laws (by Coursework and Research), 2021